Spatial variability of soil respiration in the semi-arid wetland Las Tablas de Daimiel (Spain) - Sánchez-Carrillo, Salvador (Supplement to: Sánchez-Carrillo, S (submitted): Soil respiration in the spatial realm: an example from semiarid wetlands. PeerJ, 2018)
Soil respiration measurements and soil characterizacion data in two field campaings carried out in Las Tablas de Daimiel wetland (Spain) during August 2008 and February 2009. The field campaing included high spatial resolution measurements (simultaneous records at different locations).